The Kantian sublime : from morality to art - Crowther, Paul (Oxford : Clarendon Press, 1989)
Publisher description:##With this, the first volume in the Oxford Philosophical Monographs series, Paul Crowther breaks new ground by providing what is probably the first study in any language to be devoted exclusively to Kant's theory of the sublime. It fills a gap in an area of scholarship where Kant makes crucial links between morality and aesthetics and will be particularly useful for Continental philosophers, among whom the Kantian sublime is currently receiving widespread discussion in debates about the nature of postmodernism. Crowther's arguments center on the links which Kant makes between morality and aesthetics, and seek ultimately to modify Kant's approach in order to establish the sublime as a viable aesthetic concept with a broader cultural significance.
boek
Keywords: Kant, Immanuel